Identification of the differentially expressed genes in the leg muscles of Zhedong white geese (Anser cygnoides) reared under different photoperiods - Moran Hu; Hangfeng Jin; Jianqing Wu; Xiaolong Zhou; Songbai Yang; Ayong Zhao; Han Wang (Poultry Science, 2022)
ABSTRACT: Light is a factor affecting muscle development and meat quality in poultry production. However, few studies have reported on the role of light in muscle development and meat quality in geese. In this experiment, 10 healthy 220-day-old Zhedong white geese were reared for 60 d under a long photoperiod (15L:9D, LL) and short photoperiod (9L:15D, SL). The gastrocnemius muscles were collected after slaughter to evaluate muscle fiber characteristics and meat color, and RNA-seq analysis. The results showed that compared to the LL group, the SL group had large muscle fiber diameter and cross-sectional area, few muscle fibers per unit area, high meat color a* value, and low L* value at 24 h postmortem. On comparing the 2 groups, 70 differentially expressed genes (DEGs) were identified. Compared to the SL group, the LL group had 25 upregulated and 45 downregulated genes. Gene Ontology (GO) enrichment analysis showed that these DEGs were mainly involved in cell, cell part, binding, cellular processes, and single-organism processes. Several significantly enriched athways were identified in the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis, such as the calcium and PI3k-Akt signaling pathways. The expression of five randomly selected DEGs was verified using quantitative real-time PCR, and the results were consistent with the RNA-seq data. This study provides a theoretical basis for studying the molecular mechanisms by which light affects muscle development and meat color in geese.